AN ANALYSIS OF THE USE OF DICTION ON EMPHATY STATEMENT IN GOODENOUGHPARENTS.ID - Rose Diana (Asosiasi Dosen Muda Indonesia, 2023)
In this research, the writer aims to analyze the use of diction of gentle parenting sentences in GoodEnoughparents.id. This study analyzes the diction based on Gorys Keraf theory which includes (1) diction based on meaning consist of denotation and connotation, (2) diction based on lexical issues, especially in terms of formal and informal diction in gentle parenting conversation/sentences , and (3) the function of diction in gentle parenting sentences/conversation. The research method used is a descriptive qualitative method. The object in this research is dictions in the form of words, phrases, clauses, and sentences in Goodenoughparents.id both in web or instagram posts. Data collection was conducted by reading, classifying, and analyzing. The validity of this data in this study was obtained through observation, discussion, and sufficient references. There are four research results found based on the data analysis. First, the type of diction used in Goodenoughparents.id instagram posts is diction which has denotative and connotative meanings, but most of the dictions (90%) of the instagram posts use denotative dictions. Second, the researcher found that in terms of lexical structure, there are only formal and informal dictions and the usage of formal and informal diction in goodenoughparetns.id instagram posts are equal. Third, the function of diction in gentle parenting conversation or sentences is to ensure that the communication between parents and children can run smoothly, through denotative dictions in pretend play activities or through informal dictions that is popular among children.